Pleiotropic impact of DNA-PK in cancer and implications for therapeutic strategies - Dylgjeri, Emanuela (Clin Cancer Res, 2019)
PURPOSE: DNA-dependent protein kinase catalytic subunit (DNA-PK) is a pleiotropic kinase involved in DNA repair and transcriptional regulation. DNA-PK is deregulated in selected cancer types, and is strongly associated with poor outcome. The underlying mechanisms by which DNA-PK promotes aggressive tumor phenotypes are not well understood. Here, unbiased molecular investigation in clinically relevant tumor models reveal novel functions of DNA-PK in cancer. EXPERIMENTAL DESIGN: DNA-PK function was modulated using both genetic and pharmacologic methods in a series of in vitro models, in vivo xenografts, and patient derived explants (PDEs), and the impact on downstream signaling and cellular cancer phenotypes was discerned. Data obtained were used to develop novel strategies for combinatorial targeting of DNA-PK and hormone signaling pathways. RESULTS: Key findings reveal that: i) DNA-PK regulates tumor cell proliferation; ii) pharmacological targeting of DNA-PK suppresses tumor growth both in vitro, in vivo and ex vivo; iii) DNA-PK transcriptionally regulates known DNA-PK-mediated functions as well as novel cancer-related pathways that promote tumor growth; iv) dual targeting of DNA-PK/TOR kinase (TORK) transcriptionally up-regulates androgen signaling, which can be mitigated using the AR antagonist, Enzalutamide; v) co-targeting AR and DNA-PK/TORK leads to the expansion of anti-tumor effects, uncovering modulation of novel, highly relevant pro-tumorigenic cancer pathways; and viii) co-targeting DNA-PK/TORK and AR has cooperative growth inhibitory effects in vitro and in vivo. CONCLUSION: These findings uncovered novel DNA-PK transcriptional regulatory functions and led to the development of a combinatorial therapeutic strategy for advanced prostate cancer patients, currently being tested in the clinical setting.